2019
DOI: 10.11114/jets.v7i2.3764
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Respiratory Muscle Training on Aerobic and Anaerobic Strength in Adolescent Taekwondo Athletes

Abstract: This study was conducted to investigate the effect of respiratory muscle training on respiratory functions and aerobic and anaerobic strength in adolescent taekwondo athletes. Between the ages of 12–17, 32 taekwondo athletes participated in the study. Participating athletes were randomly divided into two groups as ‘’experimental group’’ (n=15) and ‘’control group’’ (n=17) as to similar characteristics. The experimental group was given respiratory muscle training for 30 min with an adjustable respiratory pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, some studies showed improvement in FEV1 after IMT ( Mackala et al, 2019 ). Koc and Saritas (2019) reported a significant increase in FEV1 and MVV values after IMT in favor of the experimental group, with p < 0.05. Hajghanbari et al (2013) , in a review of 21 papers, also reported significant increment in FEV1 and MVV after IMT and no significant change in FVC.…”
Section: Discussionmentioning
confidence: 88%
“…However, some studies showed improvement in FEV1 after IMT ( Mackala et al, 2019 ). Koc and Saritas (2019) reported a significant increase in FEV1 and MVV values after IMT in favor of the experimental group, with p < 0.05. Hajghanbari et al (2013) , in a review of 21 papers, also reported significant increment in FEV1 and MVV after IMT and no significant change in FVC.…”
Section: Discussionmentioning
confidence: 88%
“…19 handball players participated in the study of Hartz et al At the end of the study, they explained that there was a significant difference in MVV values 37 . After 8 weeks of respiratory muscle training in Taekwondo athletes, it was seen that maximum voluntary ventilation increased in the experimental group 38 . In another study conducted on 20 healthy people, they stated that there was a significant difference in VC values at the end of the study 39,40,41 .…”
Section: Discussionmentioning
confidence: 90%
“…In another study conducted on 20 healthy people, they stated that there was a significant difference in VC values at the end of the study 39,40,41 . Koç, Stated that there is no statistically significant difference in ERV after respiratory muscle training on Taekwondo athletes 38 .…”
Section: Discussionmentioning
confidence: 97%
“…The input variable in the model is training "dose" (amount and intensity), and the output variable is performance. 4 Achievement is the result of a combination of adaptation and fatigue. This result aims to describe the effect of training load as two antagonistic functions of adaptation and fatigue.…”
Section: Application Of Banister Model In Training Practicementioning
confidence: 99%